Delay in diagnosis of cancer in Iraq: Implications for survival and health outcomes at Children’s Welfare Teaching Hospital in Baghdad - Widad Yadalla; Mazin F. Al-Jadiry; Safaa A. Faraj; Hasanein H. Ghali; Aaron Shakow; Muhummed N. Kasmani; Mary C. Smith Fawzi; Salma A. Al-Hadad (Journal of Global Health Reports)
# Background